Bureaucracy Reform, Community Participation and E-Bureaucracy under Regent Winesa and Regent Putu Artha in Jembrana, Bali - Utomo, Haryo Ksatrio; Cinderakasih, Mega Indah; Soebagjo, Natalie (Makara Human Behavior Studies in Asia, 2015)
The use of technology in reforming the government bureaucracy, namely e-Bureaucracy in the regency of Jembrana raises the assumption that the modernization of the bureaucracy can be supported by the social system based on cultural values. It is assumed that the implementation of e-Bureaucracy since the leadership of Regent I Gede Winesa was able to reform the bureaucracy in Jembrana. However, the latest research of his successor’s leadership suggests that there is the potential for failure of e-Bureaucracy, ranging from a decrease in function of the J-Net tower, the non-functioning of the rural internet office, and the return to manual service. The results showed that there are two basic problems in the implementation of e-Bureaucracy. First, the lack of sustained internal reform in Jembrana. This condition is caused by the euphoria with the past government and by the lack of innovation by the Jembrana bureaucratic apparatus. This situation is caused by the limited delegation of power in the bureaucratic structure in Jembrana. Secondly, community participation is not really being optimized as the basis of external reform. The lack of community participation is caused by the strong top-down approach from government and the lack of empowerment building by local NGO. The study uses a qualitative approach supplemented with literature study, in-depth interviews, and focus group discussions (FGD).